Scooby-Doo! music of the vampire : original movie - Block, David, director; Bennett, Jeff, 1962-; Cohn, Mindy, 1966-; Cummings, Jim, 1952-; Barbera, Joseph; Hanna, William, 1910-2001. (Burbank, CA : Warner Home Video, 2012)
Scooby and the gang attend a vampire festival and discover that one of the other guests is a real vampire intent on making Daphne his bride.
Based on characters created by Joseph Barbera and William Hanna.
Originally released as a motion picture direct-to-video in 2012.
Features: Scooby-Doo sing-along, UltraViolet digital copy.
Voices: Jeff Bennett, Mindy Cohn, Jim Cummings, Rob Paulsen, Mindy Sterling.
MPAA rating: Not rated.
DVD, Dolby digital 5.1 surround.
Keywords: Barbera, Joseph -- Film adaptations; Hanna, William, -- 1910-2001 -- Film adaptations; Scooby-Doo (Fictitious character) -- Drama; Vampires -- Drama; Private investigators -- Drama; Detective and mystery films; Video recordings for the hearing impaired; Fiction films; Based on the book; Feature films; Animated films; Comedy films; Detective films; Mystery films